Acute effects of short-term local tendon vibration on plantar flexor torque, muscle contractile properties, neuromuscular and brain activity in young athletes - Zinke, F.; Gebel, A.; Granacher, U.; Prieske, O. (Journal of Sports Science & Medicine, 2019)
The purpose of this study was to examine the acute effects of short-term Achilles tendon vibration on plantar flexor torque, twitch contractile properties as well as muscle and cortical activity in young athletes. Eleven female elite soccer players aged 15.6 ± 0.5 years participated in this study. Three different conditions were applied in randomized order: Achilles tendon vibration (80 Hz) for 30 and 300 s, and a passive control condition (300 s). Tests at baseline and following conditions included the assessment of peak plantar flexor torque during maximum voluntary contraction, electrically evoked muscle twitches (e.g., potentiated twitch peak torque [PT]), and electromyographic (EMG) activity of the plantar flexors. Additionally, electroencephalographic (EEG) activity of the primary motor and somatosensory cortex were assessed during a submaximal dynamic concentric-eccentric plantar flexion exercise using an elastic rubber band. Large-sized main effects of condition were found for EEG absolute alpha-1 and beta-1 band power (p = 0.011; 1.5 = d =2.6). Post-hoc tests indicated that alpha-1 power was significantly lower at 30 and 300 s (p = 0.009; d = 0.8) and beta-1 power significantly lower at 300 s (p < 0.001; d = 0.2) compared to control condition. No significant effect of condition was found for peak plantar flexor torque, electrical evoked muscle twitches, and EMG activity. In conclusion, short-term local Achilles tendon vibration induced lower brain activity (i.e., alpha-1 and beta-1 band power) but did not affect lower limb peak torque, twitch contractile properties, and muscle activity. Lower brain activity following short-term local Achilles tendon vibration may indicate improved cortical function during a submaximal dynamic exercise in female young soccer players.